Program Literasi Berbasis Web Sebagai Upaya Menumbuhkan Budaya Literasi Masyarakat Kelurahan Nagarasari Di Kota Tasikmalaya Jawa Barat - Setyo Wati (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The low literacy of the Indonesian people is a situation which is inversely proportional to the age of the Indonesian people who have developed that should have the same literacy levels as other developing countries, but Indonesia is still far behind as a survey conducted by UNESCO in 2016. This situation can occur due to internal and external factors. One of external factors is the lack of public services related to education, both formal and informal. It also happened in Nagarasari Village in the City of Tasikmalaya, West Java. In the city of Tasikmalaya, there found a community reading park (TBM), but it has not been yet productive in providing literacy programs to the surrounding community. Even though the existence of community reading parks in the community is a part of education. Knowing this phenomenon, it is necessary to have an effective solution to develop and advance the welfare of society. This community service activity is carried out using real action activities methods, namely web-based literacy programs by collaborating between teaching, training, community development, and web-based literacy programs in the community. It is hoped that this activity can foster a culture of community literacy, hence this can be a useful solution in the community to encourage improvements in quality of life, creativity, independence, and competitiveness in the future